Israel and the Question of Reparations from Germany Post-Holocaust Reckonings (1949-1953) - Tovy, Jacob (De Gruyter, 2023)
Based on an extensive range of primary sources - whether they be archival, journalistic or documentary - some of which are exposed here for the first time, the present volume reviews the efforts made by the State of Israel to obtain reparations from Germany after the Holocaust, as well as the unprecedented storm which this issue caused among Israeli Jews. It is the most comprehensive research work undertaken in any language on this subject.